A Physical Chemistry Study of Black Powder Materials by Solution Combustion Synthesis Method - Fitria Hidayanti; Kiki R. Lestari; Nano Sujani; Jarot Raharjo (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2021)
A study on the synthesis of black powder (La2NiO4) material using the solution combustion synthesis method at a variation of synthesis temperature of 60, 70, and 80°C was carried out. It produces a mass of black powder of 2 grams by four times of synthesis process. Then, material characterization was performed on the black powder samples obtained by using X-ray Diffraction (XRD) to determine the phases formed, Scanning Electron Microscopy - Energy Dispersive X-ray Spectroscopy (SEM-EDS) to determine the morphology and analyze the composition elemental on the microscale and Fourier Transform Infra-Red (FTIR) to determine chemical bonds. From the whole black powder sample, XRD analysis showed the phases of Dilantanum Nickel Tetraoxide (La2NiO4), Nickel Oxide (NiO), Lanthanum Oxide (La2O3), and Lanthanum Oxide Ht x-form (La2O3 Ht (x-form)). In addition, it was seen from the visible compositions of the phases that the NiO phase looks more dominant and the variation of the synthesis temperature shows that the La2O3 phase was increasing. This was supported by the EDS analysis, which showed that the EDS spectrum contains elements La, Ni, and O where the element O indicates that oxidation occurs in the elements Ni and La. On the other hand, the SEM analysis results confirm that the black powder sample contains the elements La and Ni, based on the high and low electron images contained in the morphology of the black powder sample. In addition, it was also known that the particles in the black powder sample were micron size and had porous morphology. This occurs due to rapid thermal decomposition events and excessive gas development. In addition, FTIR analysis showed that the O-H bond had been reduced and there are still C-O and C-H bonds indicating the presence of organic elements possessed by glycine.